Influences of 12-Week Physical Activity Interventions on TMS Measures of Cortical Network Inhibition and Upper Extremity Motor Performance in Older Adults—A Feasibility Study - McGregor, Keith M.; Crosson, Bruce; Mammino, Kevin; Omar, Javier; García, Paul S.; Nocera, Joe R. (Frontiers in Aging Neuroscience, 2018)
Objective: Data from previous cross-sectional studies have shown that an increased level of physical fitness is associated with improved motor dexterity across the lifespan. In addition, physical fitness is positively associated with increased laterality of cortical function during unimanual tasks; indicating that sedentary aging is associated with a loss of interhemispheric inhibition affecting motor performance. The present study employed exercise interventions in previously sedentary older adults to compare motor dexterity and measure of interhemispheric inhibition using transcranial magnetic stimulation (TMS) after the interventions. Method: Twenty-one community-dwelling, reportedly sedentary older adults were recruited, randomized and enrolled to a 12-week aerobic exercise group or a 12-week non-aerobic exercise balance condition. The aerobic condition was comprised of an interval-based cycling “spin” activity, while the non-aerobic “balance” exercise condition involved balance and stretching activities. Participants completed upper extremity dexterity batteries and estimates of VO2max in addition to undergoing single (ipsilateral silent period - iSP) and paired-pulse TMS (ppIHI) in separate assessment sessions before and after study interventions. After each intervention during which heart rate was continuously recorded to measure exertion level (load), participants crossed over into the alternate arm of the study for an additional 12-week intervention period in an AB/BA design with no washout period. Results: After the interventions, regardless of intervention order, participants in the aerobic spin condition showed higher estimated VO2 max levels after the 12-week intervention as compared to estimated VO2max in the non-aerobic balance intervention. After controlling for carryover effects due to the study design, participants in the spin condition showed longer ipsilateral silent period duration than the balance condition. Heart rate load was more strongly correlated with silent period duration after the Spin condition than estimated VO2. Conclusions: Aging-related changes in cortical inhibition may be influenced by 12-week physical activity interventions when assessed with the ipsilateral silent period. Although inhibitory signaling is mediates both ppIHI and iSP measures each TMS modality likely employs distinct inhibitory networks, potentially differentially affected by aging. Changes in inhibitory function after physical activity interventions may be associated with improved dexterity and motor control at least as evidence from this feasibility study show.